2016
DOI: 10.21608/zumj.2016.4646
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Postburn Contracture of First Web Space of the Hand

Abstract: Background: Soft tissue reconstruction of the first web space remained a challenge for plastic and reconstructive surgeons. First web space adduction contractures are a common consequence of hand burns. Many reconstructive techniques are used and investigation for more effective methods continues. Objective: assess the range of movement as regard opposition, palmar abduction and thumb extension. Also assessed the depth of web space after reconstruction of post burn contracted first web space to ass the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
0
0
2
Order By: Relevance
“…In the current study, the degree of angle of first web space was significantly increased six months post-Y-V plasty in most patients (p<0.001). This finding was similar to Ahmed's 2016 study (17) in Egypt, who reported that after five flap z-plasty, skin graft and groin pedicle flap for patients with first web space contracture, most of the patients achieved a full range of movement, but not for patients with affected joints (23) .…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the degree of angle of first web space was significantly increased six months post-Y-V plasty in most patients (p<0.001). This finding was similar to Ahmed's 2016 study (17) in Egypt, who reported that after five flap z-plasty, skin graft and groin pedicle flap for patients with first web space contracture, most of the patients achieved a full range of movement, but not for patients with affected joints (23) .…”
Section: Discussionsupporting
confidence: 89%
“…handeln, 6 Fälle konnten mit Vollhauttransplantaten und weitere 8 mit gestielten Leistenlappen erfolgreich versorgt werden [31]. Diese beiden Arbeiten beziehen sich ausschließlich auf Verbrennungskontrakturen und beinhalten keine posttraumatischen Zustände anderer Genese und haben damit sicher einen gewissen Auswahl-Bias.…”
Section: Operative Behandlungunclassified
“…Gemäss Fraulin und Thomson ist die 120-Grad-4-Lappen-Z-Plastik diejenige Z-Plastik, die den größten Längengewinn für die Kommissur und somit auch die größte Vertiefung bringt, aber im Vergleich zur 90-Grad-4-Lappen-Z-Plastik auch deutlich schwieriger zu verschließen ist [25]. Ahmed konnte von 35 Fällen mit Verbrennungskontrakturen speziell der ersten Kommissur 21 Fälle mit Z-Plastiken mit unterschiedlicher Lappenzahl (2 oder 5 Lappen) be-handeln, 6 Fälle konnten mit Vollhauttransplantaten und weitere 8 mit gestielten Leistenlappen erfolgreich versorgt werden [31]. Diese beiden Arbeiten beziehen sich ausschließlich auf Verbrennungskontrakturen und beinhalten keine posttraumatischen Zustände anderer Genese und haben damit sicher einen gewissen Auswahl-Bias.…”
Section: Operative Behandlungunclassified